Psychological assessment of the caregivers of women with cancer through the General Comfort Questionnaire - Rezende, Vera Lucia; Derchain, Sophie; Botega, Neury José; Sarian, Luis Otávio; Vial, Daniela Landulfo; Morais, Sirlei Siani; Perdicaris, Antonio André Magoulas (Paidéia (Ribeirão Preto), 2010)
This study evaluated global well-being of 133 caregivers of women with genital or breast cancer in the advanced stage of disease through the General Comfort Questionnaire (GCQ) and evaluates the association with anxiety, depression, sociodemographic characteristics; and incumbencies of the main caregivers. The Hospital Anxiety and Depression Scale was completed, followed by the GCQ and an interview semi-structured. To assess the effects of the caregivers characteristics on GCQ scores, analysis of variance followed by Tukey were applied. Stepwise multiple linear regressions were used. The Cronbachs Alpha coefficient was 0.8315. Older caregiver presented better comfort (p